Pre-plasma remobilization of ferromagnetic dust in FTU and possible interference with tokamak operations. (4th September 2019) - De Angeli, M.; Lazzaro, E.; Tolias, P.; Ratynskaia, S.; Vignitchouk, L.; Castaldo, C.; Apicella, M.L.; Gervasini, G.; Giacomi, G.; Giovannozzi, E.; Granucci, G.; Iafrati, M.; et al.
Abstract: Experimental evidence of the pre-plasma remobilization of ferromagnetic dust in FTU is presented. Thomson scattering data and IR camera observations document the occurrence of intrinsic dust remobilization prior to discharge start-up and allow for a rough calculation of the average mobilized dust density. Exposures of calibrated extrinsic non-magnetic and ferromagnetic dust to sole magnetic field discharges reveal that the magnetic moment force is the main mobilizing force, as confirmed by theoretical estimates. Pre-plasma remobilization probabilities are computed for varying dust sizes. The impact of prematurely remobilized dust on the breakdown and burn-through start-up phases is investigated together with the discharge termination induced once the plasma plateau is established.